Screw dislocation-induced pyramidal crystallization of dendron-like macromolecules featuring asymmetric geometry. Issue 36 (17th August 2021) - Sun, Xinyu; Feng, Xueyan; Yan, Xiao-Yun; Luo, Jiancheng; Zhang, Ruimeng; Li, Tao; Li, Hui; Chen, Jiahui; Liu, Fangbei; Raee, Ehsan; Cheng, Stephen Z. D.; Liu, Tianbo
Abstract : The dendron-shaped macromolecules AB n crystallize into well-ordered pyramid-like structures from mixed solvents, which is on the contrary to spherical motifs with curved structures in bulk. Abstract : We report herein that dendron-shaped macromolecules AB n crystallize into well-ordered pyramid-like structures from mixed solvents, instead of spherical motifs with curved structures, as found in the bulk. The design of the asymmetric molecular architecture and the choice of mixed solvents are applied as strategies to manipulate the crystallization process. In mixed solvents, the solvent selection for the Janus macromolecule and the existence of dominant crystalline clusters contribute to the formation of flat nanosheets. Whereas during solvent evaporation, the bulkiness of the asymmetric macromolecules easily creates defects within 2D nanosheets which lead to their spiral growth through screw dislocation. The size of the nanosheets and the growth into 2D nanosheets or 3D pyramidal structures can be regulated by the solvent ratio and solvent compositions. Moreover, macromolecules of higher asymmetry generate polycrystals of lower orderliness, probably due to higher localized stress.